RNA-Guided AsCas12a-and SpCas9-Catalyzed Knockout and Homology Directed Repair of the Omega-1 Locus of the Human Blood Fluke, Schistosoma mansoni - Wannaporn Ittiprasert (2022)
The efficiency of the RNA-guided AsCas12a nuclease of Acidaminococcus sp. was compared with SpCas9 from Streptococcus pyogenes, for functional genomics in Schistosoma mansoni. We deployed optimized conditions for the ratio of guide RNAs to the nuclease, donor templates, and electroporation parameters, to target a key schistosome enzyme termed omega-1. Programmed cleavages catalyzed by Cas12a and Cas9 resulted in staggered-and blunt-ended strand breaks, re-spectively. AsCas12a was more efficient than SpCas9 for gene knockout, as determined by TIDE analysis. CRISPResso2 analysis confirmed that most mutations were deletions. Knockout efficiency of both nucleases markedly increased in the presence of single-stranded oligodeoxynucleotide (ssODN) template. With AsCas12a, ssODNs representative of both the non-CRISPR target (NT) and target (T) strands were tested, resulting in KO efficiencies of 15.67, 28.71, and 21.43% in the SpCas9 plus ssODN, AsCas12a plus NT-ssODN, and AsCas12a plus T-ssODN groups, respectively. Trans-cleavage against the ssODNs by activated AsCas12a was not apparent in vitro. SpCas9 catalyzed more precise transgene insertion, with knock-in efficiencies of 17.07% for the KI_Cas9 group, 14.58% for KI_Cas12a-NT-ssODN, and 12.37% for KI_Cas12a-T-ssODN. Although AsCas12a induced fewer mutations per genome than SpCas9, the phenotypic impact on transcription and expression of omega-1 was similar for both nucleases.